Fluorescence Labelling of Proteomic Samples - Sen, Srijon (International Journal Of Chemistry, Mathematics And Physics(IJCMP), 2022)
Over the decades, covalent derivatization of proteins with fluorescent dyes prior to separation is widely used in the field of proteomic research. Our work examines the reactivity of a novel fluorescent dye with different proteins having different properties and check out for the reaction time of this dye with the proteins. Several experiments suggested that the reaction is increasing with time. Phosphate Buffer turned out to be a better option compared to Tris Buffer in terms of protein solubilization. Denaturing and non-denaturing gel electrophoresis suggested that the fluorescent dye reacts with Lysozyme, Bovine Serum Albumin and mammalian Red Fluorescent Protein but does not bind with Ubiquitin. Matrix assisted laser desorption/ionization-mass spectrometry also demonstrated in support of the gel electrophoresis results. The internal fluorescence property of the red fluorescent protein remained intact in the presence of this dye. This fluorescent dye can most likely be considered as a cysteine-specific dye. In many ways, fluorescence-labeling of cysteine residues presents a more attractive alternative than labeling any other residues. Serial dilution studies suggested that the sensitivity of this dye is high and can detect as low as 20 ng of BSA. Thereby, this novel fluorescent dye may serve as an alternative for labeling proteins where atleast one cysteine residue is present.